Mobile Class Attendance System (MobCAS) / Nurul Hafizah Zainal Abidin ... [et al.] - Zainal Abidin, Nurul Hafizah; Muhamidon, Muhammad Ridhwan; Abdul Halim, Bushra; Arsad, Roslah (Universiti Teknologi MARA, Perak, 2021)
People nowadays choose to use mobile applications in their daily tasks. Due to COVID19 pandemic, students and lecturers faced a new challenge in learning and teaching, which have to be conducted online. One critical issue in online and distance learning is to monitor the students attendance. Google meets has been widely used but few problems emerged such as limited in notifying absenteeism. Therefore, this study aims to develop a smartphone application called MobCAS that can be used to record student attendance and to calculate the percentage of attendance automatically for reporting the absenteeism. This mobile application was created on the Android platform and communicates with a webserver using phpMyAdmin as the database platform. This paper provides the fundamental design and implementation of MobCAS. The results from users survey indicated that the system is easy to operate, effective and acceptable to use in the future.